A STUDY OF ROLE OF TECHNOLOGY IN RETAIL MANAGEMENT - Panday, Amitabh (International Journal of Multidisciplinary Research and Studies, 2020)
When each of these components is brought together, the end result is the construction of a solid base that serves as an excellent foundation for ensuring that the opportunity is utilized to its fullest potential. When all of these elements are brought together, the end result is the construction of a solid base. One type of business plan that could potentially benefit from the opportunities is one that describes a retail establishment that uses the internet as the platform to deliver their goods and services to customers. This type of plan is an example of a business plan that could potentially profit from the possibilities. Notably, the adoption of this sort of business model would call for the construction of highly developed technological structures that would boost the pace at which products could be transferred and the number of individuals who had access to information that was pertinent to the situation. As a direct result of this, the utilization of a broad array of business tools and software, such as NCR Counterpoint, would be of the utmost significance in order to make the most of the opportunities that the possibility presented